Development of the Application Course on Social Studies Religion and Culture Subject on the Topic of Good Buddhist for Grade 2 Student in Watthaichumphon Municipality School - Kaewkor, Chatyanin; Phomsorn, Suphawadee; Meesup, Phutcharawalai; Jarernvongrayab, Anu; Voravitrattanakul, Piyamanas (Humanities and Social Sciences Journal of Pibulsongkram Rajabhat University, 2021)
The purposes of this research were to: 1) develop and find the quality of application on Social Studies Religion and Culture subject on the topic of Good Buddhist, 2) compare learning achievement in Social Studies Religion and Culture on the topic of Good Buddhist before and after learning by using application, and 3) study students’ satisfaction towards learning activities by using application. The sample consisted of 41 students Grade 2/2 during the academic year 2019 of Watthaichumphon Municipality School. The instruments of this research were: 1) application in Social Studies Religion and Culture on the topic of Good Buddhist, 2) the achievement test, and 3) questionnaires on satisfaction towards learning activities by using application The statistical analysis employed was mean, standard deviation, and t–test dependence. The results of this research were as follows: 1) develop quality of application in Social Studies Religion and Culture subject on the topic of Good buddhist had extremely high level in subject section ( = 4.77, S.D. = 0.19), had extremely high level in technical section ( = 4.81, S.D. = 0.25) 2) The learning achievement on Good Buddhist of Grade 2 students after learning by using application were statistically significant higher than before learning at .05 level. 3) The students’ satisfaction towards learning activities by using application on Good Buddhist one information were at a high level ( = 4.45, S.D. = 0.54) on the aspects of learning activities were at the extremely high, followed by forms of media.